(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Baptist Theological Seminary - An Example of Integrity and Assertion of Freedoms of Conscience Through this study we want to present some data from the history of the Baptist Theological Seminary in Romania on the account of integrity and religious freedom. Founded in 1921, it continued its existence under this name until 1990 when it was transformed into a Theological Institute with a university fence. This was achieved after the December 1989 Revolution, which brought much-needed religious freedom. At the same time, the Baptist Theological Seminary and then the Baptist Theological Institute together with the Faculty of Baptist Theology have offered and continue to offer trust, support to those in need, to promote integrity and to campaign for respect for the fundamental rights and freedoms of man and citizen among which and religious freedom.